Effectiveness of an individually tailored complex intervention to improve activities and participation in nursing home residents with joint contractures (JointConEval): a multicentre pragmatic cluster-randomised controlled trial - Nguyen, Natalie; Thalhammer, Regina; Meyer, Gabriele; Le, Lien Dung; Mansmann, Ulrich; Vomhof, Markus; Skudlik, Stefanie; Beutner, Katrin; Müller, Martin (BMJ open, 2023)
Objective This study aims to examine the effects of the individually tailored complex intervention Participation Enabling Care in Nursing (PECAN) on activities and participation of residents with joint contractures. - Design Multicentre pragmatic cluster-randomised controlled trial. - Setting 35 nursing homes in Germany (August 2018-February 2020). - Participants 562 nursing home residents aged ≥65 years with ≥1 major joint contracture (303 intervention group, 259 control group). - Interventions Nursing homes were randomised to PECAN (18 clusters) or optimised standard care (17 clusters) with researcher-concealed cluster allocation by facsimile. The intervention targeted impairments in activities and participation. Implementation included training and support for selected staff. Control group clusters received brief information. - Primary and secondary outcome measures The primary endpoint PaArticular Scales combined residents’ activities and participation at 12 months. The secondary outcome comprised quality of life. Safety measures were falls, fall-related consequences and physical restraints. Residents, staff and researchers were unblinded. Data collection, data entry and statistical analysis were blinded. Primary analyses were intention-to-treat at cluster level and individual level using a generalised mixed-effect regression model and imputation of missing data. - Results Primary outcome analyses included 301 intervention group residents and 259 control group residents. The mean change on the Activities Scale was −1.47 points (SD 12.2) in the intervention group and 0.196 points (SD 12.5) in the control group and −3.87 points (SD 19.7) vs −3.18 points (SD 20.8) on the Participation Scale. The mean differences of changes between the groups were not statistically significant: Activities Scale: −1.72 (97.5% CI −6.05 to 2.61); Participation Scale: −1.24 (97.5% CI −7.02 to 4.45). We found no significant difference in the secondary outcome and no effects on safety measures. - Conclusion The complex intervention did not improve the activities and participation of nursing home residents on the PaArticular Scales at 12 months. Current nursing conditions in Germany may hamper implementation. - Trial registration number DRKS00015185.